Bridging the Grammar-Law Gap: Active Learning for Arabic Legal Texts in Indonesian Islamic Universities - Muhammad Majduddin; Mohammad Makinuddin; Mohammed Ramadhan Abraheem Alshaykh Ali (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2026)
A persistent gap remains in Indonesian Islamic higher education between teaching Arabic grammar (nahwu) and applying it to authentic Islamic legal discourse, as most instruction relies on decontextualized, fabricated sentences that fail to prepare students for interpreting real legal texts. Prior studies have examined Arabic instruction or active learning separately but have not developed a systematic, empirically grounded model that explicitly links grammatical competence to legal text analysis and authentic assessment. This study aims to develop and examine an active learning model grounded in Islamic law at UNKAFA Gresik. Using a qualitative phenomenological approach, data were collected through interviews, observations, and documentation involving 10 students and 2 lecturers, and then analyzed thematically. The findings reveal that a structured model combining group-based text analysis with guided worksheets significantly enhances both grammatical mastery and contextual legal understanding, though an evaluation gap remains, as exams still prioritize artificial sentences over authentic texts. This study concludes that integrating active learning successfully creates lecturer-initiated contextual activities, student-centered text analysis, and collaborative learning models, and recommends adopting authentic text-based assessment and aligning the institutional curriculum to strengthen epistemological coherence in Arabic language education. Terdapat kesenjangan persisten di perguruan tinggi Islam Indonesia antara pengajaran tata bahasa Arab (nahwu) dan penerapannya pada wacana hukum Islam yang autentik, karena sebagian besar pembelajaran masih menggunakan kalimat buatan yang tidak kontekstual sehingga gagal mempersiapkan mahasiswa untuk interpretasi teks hukum yang sesungguhnya. Penelitian sebelumnya membahas instruksi bahasa Arab atau pembelajaran aktif secara terpisah, namun belum mengembangkan model sistematis berbasis empiris yang secara eksplisit menghubungkan kompetensi tata bahasa dengan analisis teks hukum dan penilaian autentik. Penelitian ini bertujuan mengembangkan dan mengkaji model pembelajaran aktif yang berbasis hukum Islam di UNKAFA Gresik. Menggunakan pendekatan kualitatif fenomenologis, data dikumpulkan melalui wawancara, observasi, dan dokumentasi yang melibatkan 10 mahasiswa dan 2 dosen, kemudian dianalisis secara tematik. Temuan menunjukkan bahwa model terstruktur yang menggabungkan analisis teks berbasis kelompok dan lembar kerja terpandu secara signifikan meningkatkan penguasaan tata bahasa dan pemahaman hukum kontekstual, meskipun masih terdapat kesenjangan evaluasi di mana ujian lebih mengutamakan kalimat artifisial daripada teks autentik. Penelitian ini menyimpulkan bahwa integrasi pembelajaran aktif berhasil menciptakan aktivitas kontekstual yang diprakarsai dosen, analisis teks berpusat pada mahasiswa, dan model pembelajaran kolaboratif, serta merekomendasikan adopsi penilaian berbasis teks autentik dan penyesuaian kurikulum institusional untuk memperkuat koherensi epistemologis dalam pendidikan bahasa Arab.